2007
DOI: 10.1016/j.micinf.2007.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mortality despite control of lung infection in mice aerogenically infected with a Mycobacterium tuberculosis mce1 operon mutant

Abstract: Mycobacterium tuberculosis causes a variety of host clinical outcomes. We previously showed that M. tuberculosis disrupted in an operon called mce1 proliferates unchecked in BALB/c mouse lungs. The observed outcome could be attributed either to the mutant bacterial burden or to the host immunopathologic response. To differentiate these possibilities, we studied the outcomes of infection in a mouse strain (C57BL/6) less susceptible to M. tuberculosis than BALB/c. We found that the mutant infection reached a pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…The mutant is unable to induce a strong T-helper 1 (Th1) type T cell immune response and organized granuloma formation in lungs 41 . Taken together, these observations suggest that the mce1 operon is involved in the remodeling of M. tuberculosis cell wall, dampening proinflammatory response in mouse that is associated with rapid progression to death 40,41 . The operon is not expressed in the wild type strain during the first 4-8 weeks of infection in mouse 42 , suggesting that the M. tuberculosis cell wall lipid profile can be altered according to the course and/or time of infection.…”
Section: Mycolic Acidsmentioning
confidence: 74%
See 1 more Smart Citation
“…The mutant is unable to induce a strong T-helper 1 (Th1) type T cell immune response and organized granuloma formation in lungs 41 . Taken together, these observations suggest that the mce1 operon is involved in the remodeling of M. tuberculosis cell wall, dampening proinflammatory response in mouse that is associated with rapid progression to death 40,41 . The operon is not expressed in the wild type strain during the first 4-8 weeks of infection in mouse 42 , suggesting that the M. tuberculosis cell wall lipid profile can be altered according to the course and/or time of infection.…”
Section: Mycolic Acidsmentioning
confidence: 74%
“…Both groups suggested that the operon might encode an importer system involved in recycling of MA. Also, disruption of the mce1operon renders the cells hypervirulent in mice 40,41 . The mutant is unable to induce a strong T-helper 1 (Th1) type T cell immune response and organized granuloma formation in lungs 41 .…”
Section: Mycolic Acidsmentioning
confidence: 99%
“…Tissue samples for histopathologic studies were prepared as previously described [21, 22]. Briefly, left lung was fixed in 10% buffered formalin and sectioned.…”
Section: Methodsmentioning
confidence: 99%
“…mce4a gene of mce4 operon is the most studied gene which encodes mammalian cell entry protein (Mce4A). This protein is thought to be responsible for the survival of MTB during latent infection by either importing cholesterol or by utilizing it as source of carbon and energy [15][16][17]. Several studies show that the disruption or deletion of mce operon leads to either attenuation or hypervirulence for the host [15,16,18].…”
mentioning
confidence: 99%